Disability, Fashion Design and social integration (ModaPalavra e-periódico, 2009)
This study aims to investigate solutions for the difficulties related to clothing design faced by the disable, considering the importance of normative garments for the social integration of such consumers. The secondary research is literature review and the primary research, qualitative, is a unique case study and used the interview as a way of collecting data. A unique case study implies necessarily a limited view. The results show that, for some specific disabilities, it is possible to wear clothes which are created for the non disable, as long as some fashion design resources are considered on the detriment of others. The original contribution is the search of solutions suitable for both the disable and non disable, diminishing, in this way, the differences related to clothes which may interfere in the social integration of the non disable.
Keywords: Fashion Design; Disability; Social Integration